How to Expand and Fill the Self in Organizations: The Role of Interpersonal Processes in the Employee Organizational Identity Construction - Sun, Junping; Song, Yu; Yu, Guangtao (Frontiers in Psychology, 2021)
In the era of VUCA (Volatility, Uncertainty, Complexity, and Ambiguity), the fluidity of organizations and the variability of individual work gradually replace the traditional stability and continuity. The question of how to connect employees and organizations has long intrigued researchers and practitioners. Employee organizational identity is the stable force that binds employees to organizations. Drawing on social identity theory, we argue the role of interpersonal processes in the employee organizational identity construction. We suggest that an employee’s relationship-building behaviors can promote employee organizational identity through the connected self. The indirect effect is stronger for employees who make more social comparisons because they are more sensitive to social influence. We collected data through questionnaires of 333 employees using a two-wave research design in China. The results indicate that an employee’s relationship-building behaviors enhance employee organizational identity. The connected self fully mediates the positive relationship between relationship-building and employee organizational identity. The outcomes also show that the positive effect of relationship-building toward connected self is intensified, when an employee engages in more social comparisons. The findings imply that interpersonal processes play an important role in the employee organizational identity construction. Then the theoretical and practical implications are discussed.